The family man - Cage, Nicolas, 1965-; Piven, Jeremy; Cheadle, Don.; Universal Pictures (Firm); Beacon Pictures (Universal City, CA : Universal Studios, 2001)
Jack Campbell, a workaholic Wall Street exec, gets to see what his life might have been like if he'd stayed with his former sweetheart, Kate. Thirteen years after they split up, Jack falls asleep in his posh New York apartment, then awakens to find himself a family man, with his now-wife Kate, daughter Annie and new baby.
Director of photography, Dante Spinotti ; edited by Mark Helfrich ; music by Danny Elfman ; costume designer, Betsy Heimann ; production designer, Kristi Zea.
Nicolas Cage, T?a Leoni, Jeremy Piven, Josef Sommer, Saul Rubinek, Don Cheadle.
MPAA rating: PG-13.
VHS, stereophonic surround, digitally recorded.
Closed-captioned.
Keywords: Feature films; Comedy films; Video recordings for the hearing impaired